Evaluation of maxillary anterior teeth and their relation to the golden proportion in Malaysian population - Al-Marzok, Maan Ibrahim; Abdul Majeed, Kais Raad; Ibrahim, Ibrahim Khalil (BioMed Central, 2013)
The maxillary anterior teeth are important in achieving pleasing dental aesthetics. Various methods are used to measure the size and form of them, including the golden proportion between their perceived widths, and the width-to-height ratio, referred to as the golden standard. The purpose of this study was conducted to evaluate whether consistent relationships exist between tooth width and height of the clinical crown dimensions; and to investigate the occurrence of the golden proportion of the maxillary anterior teeth. Dental casts of the maxillary arches were made in this cross-sectional study from MAHSA University College students who met the inclusion criteria. The 49 participants represented the Malaysian population main ethnics. The dimensions of the anterior teeth and the perceived width of anterior teeth viewed from front were measured using a digital caliper. Comparison of the perceived width ratio of lateral to central incisor and canine to lateral incisor with the golden proportion of 0.618 revealed there were a significant statistical difference (p < 0.05). The statistical difference was significant for the width-to-height ratio of central incisors to the golden standard of 80%. There was no significant difference in the comparison among ethnic groups for the golden proportion and the golden standard. The golden proportion was not found to exist between the perceived widths of maxillary anterior teeth. No golden standard were detected for the width-to-height proportions of maxillary incisors. Specific population characteristics and perception of beauty must be considered. However, ethnicity has no association with the proportions of maxillary anterior teeth.